A Case of Iatrogenic Cushing’s Syndrome following Use of an Over-the-Counter Arthritis Supplement - Colin Dunn; Joshua Amaya; Patrick Green (Case Reports in Endocrinology)
Background. Iatrogenic Cushing’s syndrome is commonly seen as a complication of chronic steroid use. While most often associated with the use of prescription oral steroids, rare cases result from unintentional steroid exposure. In particular, numerous complementary and alternative medicines have been found to contain steroids not previously known to users. Case Presentation. Here, we present a case of iatrogenic Cushing’s syndrome caused by prolonged ingestion of dexamethasone found within an over-the-counter arthritis supplement called Artri King. Conclusion. A thorough history of medication use to include over-the-counter medications and supplements may be required to identify the source of exogenous glucocorticoids in iatrogenic Cushing’s syndrome.